2013
DOI: 10.1007/bf03391696
|View full text |Cite
|
Sign up to set email alerts
|

Goals are Not Enough: Building Public Sector Capacity for Chronic Disease Prevention

Abstract: The rising burden of non-communicable diseases (NCDs) challenges the public health sector to develop, support and implement effective interventions to reduce this global epidemic. The United Nations has responded with a global action plan that includes goals and voluntary targets for the prevention and control of NCDs. However, setting goals is not enough. To achieve meaningful outcomes, governments must act and invest to improve key enabling capacities. Political and other public sector leadership at every ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The range of evaluated interventions represents the scope of what is commonly referred to as capacity building in a public health context. However, the papers remain focused on capacity building at the individual level, despite acknowledgement that individual behaviour is shaped by interaction with the environment at multiple levels [ 44 ], and calls to move toward system-level action [ 45 , 46 ]. Over 10 years after the 2006 WHO definition called for capacity building to happen at multiple levels, it could be expected that evaluations of capacity building would also take into account those multiple levels, and would offer some organization and system-level data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of evaluated interventions represents the scope of what is commonly referred to as capacity building in a public health context. However, the papers remain focused on capacity building at the individual level, despite acknowledgement that individual behaviour is shaped by interaction with the environment at multiple levels [ 44 ], and calls to move toward system-level action [ 45 , 46 ]. Over 10 years after the 2006 WHO definition called for capacity building to happen at multiple levels, it could be expected that evaluations of capacity building would also take into account those multiple levels, and would offer some organization and system-level data.…”
Section: Discussionmentioning
confidence: 99%
“…However the current literature included in this paper does not reflect this. A lack of system-level focus in the available literature also contrasted sharply with the call for system focus in addressing the new public health landscape [ 45 , 46 ]. A 2016 analysis of 55 public health measurement cases showed a similar focus on individual-level outcomes, finding that system-level outcomes tended to be omitted altogether since attribution was more difficult at that level [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet and alcohol. In contrast to tobacco, we found that diet and alcohol policies were similarly undermined by a lack of global accountability instruments [51,[91][92][93][94][95], a lack of globally PLOS GLOBAL PUBLIC HEALTH agreed targets and evidence, and underdeveloped mechanisms for safe industry engagement [39,[41][42][43]114].…”
Section: Plos Global Public Healthmentioning
confidence: 81%
“…The literature suggests that functioning NCD surveillance systems are critical for target setting, monitoring, planning, and to raise awareness and reinforce political commitments; however, these systems are often inadequate in FCAS, undermining policy planning [32][33][34][35][36][37][38]. Strong governance systems that facilitate multisectoral collaboration, partnership building, community mobilization, social participation, and advocacy are critical for the development of national plans, as is strong leadership to coordinate national and regional action across departments and sectors [39][40][41][42][43][44][45]. Under-prioritization of NCDs has resulted in insufficient resource allocation and the inability to finance national activities and plans [39,43,[46][47][48].…”
Section: Targets Data Collection and Plansmentioning
confidence: 99%